Konsep Islamic corporate governance sebagai tata kelola perusahaan Bakpiapia Djogja - Shofia Mauizotun Hasanah; Romi Kurniawan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2019)
Purpose — This study tries to build a paradigm and implementation of Islamic corporate governance in a company.Research method — This research uses qualitative research methods and descriptive data. The sample in this study is Bakpiapia Djogja company. The data used is a report on the implementation of Islamic corporate governance.Result — The study found that Bakpiapia Djogja company has implemented a small part of the principles contained in the concept of Islamic Corporate Governance.